INFLUENCE OF MONETARY POLICY ON STOCK MARKET DYNAMICS - Petrova, Elena; Müller , David; Johnson, Sophia (Ayden International Journal of Banking, Finance and Technology, 2024)
The study examined the impact of monetary policy on the performance of Nigerian capital market between 1985 to 2021. The time series data were extracted from Central Bank of Nigeria statistical bulletin 2022. The study employed various econometric tools such tools as Error Correction mechanism to analyse the data obtained. Stock performance as the dependent variable was proxied by market capitalization while monetary policy variables were proxied by monetary policy rate, loan to deposit ratio and liquidity ratio respectively. The results showed that all monetary policy variables employed in this study significantly relate to stock market performance. This result is in line with the quantity theory of money supply. Considering the findings, The Central Bank of Nigeria should consistently review the monetary policy variables to enhance the depth of the capital market for effective and efficient allocation and distribution of financial resources in the economy.